Public awareness of heart failure in Europe: first results from SHAPE. - Remme, W; McMurray, J; Rauch, B; Zannad, F; Keukelaar, K; Cohen-Solal, A; Lopez-Sendon, J; Hobbs, F; Grobbee, D; Boccanelli, A; Cline, C; Macarie, C; et al. (2005)
AIMS: Appropriate heart failure (HF) care and adequate resourcing require recognition of its clinical, social, and economic importance by the general public besides healthcare authorities and providers. The extent of public awareness in Europe is not known. METHODS AND RESULTS: A total of 7958 subjects were randomly selected from nine European countries (minimum 100/group per country). Each completed a 32-question survey on HF covering recognition, impact on health, comparative prevalence and severity, treatment, and costs. Although 86% of respondents had heard of HF, only 3% could correctly identify HF from a description of typical symptoms and signs, 31% correctly identified angina, and 51% identified transient ischaemic attack/stroke. Only 29% thought that HF signs and symptoms indicate a 'severe' condition. Most thought that HF patients should reduce all physical activity and 34% believed HF a normal consequence of ageing. Sixty-seven per cent thought that HF patients live longer than cancer patients. Only 9% believed that HF leads to greater healthcare expenditure than cancer, HIV, or diabetes. Overall, responses were comparable between countries. CONCLUSION: In Europe, community awareness of HF is low. Therefore, the general public is unlikely to demand appropriate measures by healthcare authorities and providers. A better understanding of HF could improve its prevention and management. Strategies to educate the public about HF are needed.